Survey of active structural control and repair using piezoelectric patches - Abuzaid, Ahmed; Hrairi, Meftah; Shaik Dawood, Mohd. Sultan Ibrahim (MDPI, 2015)
The piezoelectric actuator has gained popularity over the last few years. Attention has been directed towards the study of their electromechanical response in active repair and the control of damaged structures. This has been made possible through the development of various numerical and analytical techniques for such studies. The shift of focus towards the piezoelectric based approaches has been due to their advantages, which include strategic cost benefits in maintenance, as well as an increase in the life cycle of the repaired structures. Furthermore, adhesively bonded joints are widely used in the manufacturing and repairing of structures in many industries, especially automotive and aerospace engineering. This is due to the requirement for lightweight materials as well as the potential adhesive used to join materials with different characteristics. The piezoelectric actuator has also shown the capacity in controlling and lowering the shear stress concentration and joint edge peel in adhesively bonded joint systems. The structure’s control of stress and repair can generally be viewed as a reinforcement that influences the structure’s damage tolerance. Therefore, the interest of this review is on the applications of the piezoelectric actuators in both structural damage and the bonded adhesive joint system. The specific goal is to recognize the contemporary scientific challenges, including future opportunities.